2020
DOI: 10.1186/s12916-020-01866-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing COVID-19 surveillance in long-term care facilities: a modelling study

Abstract: Background Long-term care facilities (LTCFs) are vulnerable to outbreaks of coronavirus disease 2019 (COVID-19). Timely epidemiological surveillance is essential for outbreak response, but is complicated by a high proportion of silent (non-symptomatic) infections and limited testing resources. Methods We used a stochastic, individual-based model to simulate transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) along detailed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 78 publications
(132 reference statements)
1
66
1
2
Order By: Relevance
“…considering a time-dependent infection rate or viral load for patients after their infection, graph of relationship within the community) would be needed in order to obtain conclusive results to be used as healthcare guidelines. In this direction, based on stochastic simulations encompassing a large set of parameters, [ 68 ] also concludes on the efficiency of group testing in preventing epidemic outbreaks in health care structures.…”
Section: Discussionmentioning
confidence: 99%
“…considering a time-dependent infection rate or viral load for patients after their infection, graph of relationship within the community) would be needed in order to obtain conclusive results to be used as healthcare guidelines. In this direction, based on stochastic simulations encompassing a large set of parameters, [ 68 ] also concludes on the efficiency of group testing in preventing epidemic outbreaks in health care structures.…”
Section: Discussionmentioning
confidence: 99%
“…Populations housed in long-term care facilities are especially vulnerable to COVID-19; surveillance programs designed for these settings may have different goals and tolerances for infection risk than those designed to maintain functionality for other institutions. Smith and colleagues [ 7 ] built a complex modeling framework for long-term care facilities including simulations of the detailed inter-individual contact networks describing patient-staff interactions in such settings. This work showed that symptom-based screening by itself had limited effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…To account for possible delays in receiving test results due to laboratory processing, we also allow for a delay parameter, d . When pooling samples, we adjust for test sensitivity and applied a linear deduction for pooling of 0.00323, consistent with minimal sample dilution or degradation in a nasal or nasopharyngeal sample [ 7 ]. Other deductions may be more appropriate in different settings, such as saliva sampling [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further, with our results we envisage that random blanket testing as applied in this study would probably be a more feasible and cost effective control measure only in a very small population that is well isolated [ 6 ] and where there is enough testing capacity to test 4–10% of the population every day. In their study, a complex model created by Smith and colleagues [ 66 ] to assess optimal COVID-19 surveillance strategies in long-term care facilities also found random daily testing to be an inefficient use of resources in the long term. Therefore, overall we suggest that for such large populations as Lusaka, this control strategy would therefore be more realistically applied only besides other control measures such as intensified lock-downs, targeted testing/contact tracing, and vaccinations.…”
Section: Discussionmentioning
confidence: 99%